2023
DOI: 10.1002/tkm2.1365
|View full text |Cite
|
Sign up to set email alerts
|

The status of education for integrative medicine in Japanese medical universities with special reference to Kampo medicines

Abstract: AimThe Japanese government defined integrative/integrated medicine (IM) as “medical practice led by physicians, cooperating with other specialists.” Therefore, the basics of comprehensive medical education should be provided in medical universities. We investigated the situation of IM with special reference to Kampo medicines in the national core curricula, national examination standards and the syllabuses for lectures published on the universities' websites.MethodsIn the published documents regarding the core… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Several Kampo medicine crude drugs [1][2][3] have been analyzed to determine the primary component influencing cellular or organ function. For example, using 3D-HPLC, Kishida et al and Nakanishi et al identified the components of the Goshajinkigan extract, including morroniside, (+)-catechin, loganin, paeoniflorin, penta-O-galloylglucose, benzoylmesaconine, cinnamic acid, isoacteoside, benzoylpaeoniflorin, cinnamaldehyde, 16-ketoalisol A, and paeonol [14,16].…”
Section: Low-molecular-weight Compounds In Kampo Medicines Crude Drug...mentioning
confidence: 99%
See 1 more Smart Citation
“…Several Kampo medicine crude drugs [1][2][3] have been analyzed to determine the primary component influencing cellular or organ function. For example, using 3D-HPLC, Kishida et al and Nakanishi et al identified the components of the Goshajinkigan extract, including morroniside, (+)-catechin, loganin, paeoniflorin, penta-O-galloylglucose, benzoylmesaconine, cinnamic acid, isoacteoside, benzoylpaeoniflorin, cinnamaldehyde, 16-ketoalisol A, and paeonol [14,16].…”
Section: Low-molecular-weight Compounds In Kampo Medicines Crude Drug...mentioning
confidence: 99%
“…Kampo medicine is a Japanese traditional medicine modified and developed based on traditional Chinese medicine from the fifth to the nineteenth centuries [1][2][3]. Kampo medicines were carefully selected and developed to include various crude drugs (natural products).…”
Section: Introductionmentioning
confidence: 99%
“…Chinese name: Dang-Gui-Sheng-Jiang-Yang-Rou-Tang) to inhibit pro-inflammatory factors through AGEs-RAGE axis signaling in diarrhea-predominant irritable bowel syndrome [ 112 ]. Although Toukisyoukyouyounikuto is not contained in modern Kampo medicines because they were not described in the current Japanese Pharmacopoeia by several national laws in Japan [ 33 , 34 , 35 , 36 ], they may be focused on the effects of inhibition of AGEs-RAGE axis signaling in the future. The potential of some Kampo medicines to suppress AGEs-RAGE axis signaling has been revealed, though researchers have not made the mechanisms sufficiently clear because Kampo medicines contain various compounds that would be metabolized and treated with non-enzymic reactions ( Figure 15 ) [ 43 , 44 ].…”
Section: Effects Of Kampo Medicines On Intra- and Extracellular Agesmentioning
confidence: 99%
“…Kampo medicines are traditional medicines that were introduced from China but developed uniquely in Japan from the fifth to the nineteenth centuries [ 33 , 34 , 35 ]. Modern Kampo medicines are produced from extracts by pharmaceutical companies governed by several national laws in Japan since approximately 1950 [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%